超臨界二氧化碳環境下對套管水泥斷裂韌度影響之研究 - 陳思螢; Chen, Sih-Ying (2012)
二氧化碳存入地下以地質封存方式進行減量是一項可行的工程手段。前人研究表明二氧化碳與水結合會形成碳酸，形成一個對水泥侵蝕的酸性環境。因此評估保護井孔的套管水泥在長期的封存下是否能安全且有效的封存二氧化碳為必須進行的研究課題。 本研究針對API-G級套管水泥材料及添加飛灰之水泥材料在超臨界二氧化碳環境反應後進行試驗，先將其水泥漿體製備成巴西缺口試體，放進超臨界二氧化碳環境下 (溫度70℃、壓力20 MPa) 個別反應不同天數 (7-28天)，以模擬進行二氧化碳封存時井底下1500 m~2000 m套管水泥材料基本力學性質、斷裂力學性質及化學結構性質上之變化。實驗觀察發現隨著不同的反應天數，而試體本身有不同程度碳化現象，其中以添加飛灰之水泥有最佳的強度且有最深的碳酸鈣堆積層。 The carbon dioxide (CO2) deposition in underground geologic sequestration is a feasible approach to reduce CO2 emission Previous studies have shown that CO2 combines with water to form carbonic acid (H2CO3) which is the formation of an acidic environment of cement erosion Therefore the long-term wellbore integrity of the cement sheath should be carefully evaluated to ensure the safe and efficient storage of the CO2 In this study the Brazilian notched cement specimens along with other appropriate samples were prepared and were placed into the supercritical carbon dioxide environment over a period of days The experimental temperature is 70oC and the experimental pressure is 20 MPa The basic mechanical properties fracture mechanical properties and chemical structure properties of the API-G well cement with fly ash were investigated This study finds that the cement specimens have varying degrees of carbonization with the different number of reaction days This study also concludes that the API-G cement with fly ash displays the best strength with deepest penetrating depth of carbonization